Family-related risk indicators and dental attendance in association with dental caries in preschool children - Anna-Maria Pelkonen; Päivi Rajavaara; Hannu Vähänikkilä; Vuokko Anttonen; Marja-Liisa Laitala (BMC, 2024)
Abstract Background Determining risk indicators behind dental caries is important for identifying children in need of enhanced dental care. The aim of this register-based study was to investigate the association of family-related risk indicators and dental attendance in the development of dental caries in preschool children. Methods The data for this study were collected from the medical records of 206 randomly chosen preschool children who lived in the city of Oulu, Finland, during 2014-2020. Data on challenges in family life, missing appointments and utilization of oral health care were collected. Sum functions were formed of risk indicators. Analyses were carried out for three age groups (1- to 2-, 3- to 4- and 5- to 6-year-olds) born between 2014 and 2018. Results There was a significant association between the number of family-related risk indicators and the prevalence of manifested caries lesions in the age group of 5- to 6-year-olds. All family-related risk indicators and information about health care utilization were associated with dental caries risk. Challenges in a child's family life were present among 20.3% of the 5- to 6-year-olds. In all age groups, the most common challenges in family life were parental exhaustion and problems in the parents' relationship or divorce. Conclusion Family-related risk indicators and dental attendance should be considered when determining caries risk. The caries risk indicators investigated here are associated with each other.